(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2021)
Background: Nowadays, numerous restaurants have started operating with different and creative ideas. Apart from the chains and traditional brands of restaurants, the stand-alone variety is also emerging with modern concepts. The analysis and comparison of the performance of these stand-alone restaurants will provide insights into the market for such outlets. Objectives: The study assesses and compares the performance of stand-alone restaurants based on their operations and financial management. Methodology: The study has been carried out on two restaurants located in busy areas of Kolkata, West Bengal, India. The tools used for primary data collection are in-depth interviews with the restaurant owners, consolidated with the restaurant’s financial data. Analytical design was adopted and mathematical tool for data comparison was used. Results: It was observed that Restaurant Y performed better than Restaurant X, securing an average profit percent of 14.37% over 17 months. The other suffered an average loss of 10.28% during the same period. Patterns emerged indicating that revenue peaked during the months of September and October. Conclusion: Restaurant profiles, seating area, type of cuisine, value proposition alignment, cost structure, inventory, staff, and ticket price are important factors for a restaurant’s success. Customer sentiments impact the market, while Bengal’s Durga Puja is a driver for high revenue for such restaurants.